Sector-specific human capital and the distribution of earnings - Eric Smith (Federal Reserve Bank of Atlanta, 2009)
This paper incorporates assignment frictions and sector-specific training into the Roy model of occupational choice. Assignment frictions represent the extent of the market whereas differences in sector-specific training reflect worker specialization. This framework thus captures Adam Smith's idea that the extent of the market determines the division of labor. The paper demonstrates the way in which the relationship between assignment frictions and specialization affects the level and composition of human capital acquisition, aggregate output, and the distribution of income. Not surprisingly, economywide training, output, and specialization increase as the extent of the market increases. The distribution of these gains, however, is uneven. Within group or residual income, distribution does not converge monotonically as search frictions diminish. Comparisons across groups reveal that these effects can become more pronounced as average income increases.
Keywords: E24; J24; D31; 330; human capital; occupational choice; job assignment; income distribution